2017
DOI: 10.1002/ecs2.1785
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the population‐level impact of mitigating harbor porpoise bycatch with pingers and time‐area fishing closures

Abstract: Abstract. Unintentional mortality of higher trophic-level species in commercial fisheries (bycatch) represents a major conservation concern as it may influence the long-term persistence of populations. An increasingly common strategy to mitigate bycatch of harbor porpoises (Phocoena phocoena), a small and protected marine top predator, involves the use of pingers (acoustic alarms that emit underwater noise) and time-area fishing closures. Although these mitigation measures can reduce harbor porpoise bycatch in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…Here it was found that when AQUAmark100 pingers were used in areas of high porpoise usage, the habitat exclusion had a higher impact on the population than the bycatch in the fisheries (van Beest et al . ). These kinds of model predictions will, however, depend on the pinger type and specific effects of the pinger used.…”
Section: Discussionmentioning
confidence: 97%
“…Here it was found that when AQUAmark100 pingers were used in areas of high porpoise usage, the habitat exclusion had a higher impact on the population than the bycatch in the fisheries (van Beest et al . ). These kinds of model predictions will, however, depend on the pinger type and specific effects of the pinger used.…”
Section: Discussionmentioning
confidence: 97%
“…Independent case studies have highlighted two common impacts of such anthropogenic activities on harbour porpoises, namely, behavioural alterations (Tougaard et al 2012 ; Dyndo et al 2015 ) and direct mortality or injury of individuals (Vinther and Larsen 2004 ; Lucke et al 2009 ). To assist in the conservation of harbour porpoises, there has been increased effort to develop predictive simulation models to assess any consequences of anthropogenic stressors and disturbances on individuals and populations (Nabe-Nielsen et al 2014 ; King et al 2015 ; Aarts et al 2016 ; van Beest et al 2017 ). Such simulation models are valuable tools to highlight areas of potential conflict with current or planned anthropogenic activities and to evaluate the effectiveness of potential mitigation measures.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study suggest that the protection of key habitats for porpoises may be more straightforward than for dolphins, given their more restricted range. Successful mitigation of SSF bycatch is likely to be achieved through a combination of multiple approaches; for example, restricting fishing activities in near-shore waters, or use of acoustic alarms (pingers) on nets (e.g., van Beest et al, 2017). Indeed, a previous study has shown that pingers reduce bycatch of Peruvian small cetaceans (Mangel et al, 2013), and future work should refine the efficacy of using pingers to deter porpoises and dolphins from nets (Dawson et al, 2013).…”
Section: Conservation Implicationsmentioning
confidence: 99%